An OMV Vaccine Derived from a Capsular Group B Meningococcus with Constitutive FetA Expression: Preclinical Evaluation of Immunogenicity and Toxicity. - Gunnstein Norheim; Holly Sanders; Jardar W Mellesdal; Idunn Sundfør; Hannah Chan; Carina Brehony; Caroline Vipond; Chris Dold; Rory Care; Muhammad Saleem; Martin C J Maiden; Jeremy P Derrick; et al. (PLoS ONE)
Following the introduction of effective protein-polysaccharide conjugate vaccines against capsular group C meningococcal disease in Europe, meningococci of capsular group B remain a major cause of death and can result in debilitating sequelae. The outer membrane proteins PorA and FetA have previously been shown to induce bactericidal antibodies in humans. Despite considerable antigenic variation among PorA and FetA OMPs in meningococci, systematic molecular epidemiological studies revealed this variation is highly structured so that a limited repertoire of antigenic types is congruent with the hyperinvasive meningococcal lineages that have caused most of the meningococcal disease in Europe in recent decades. Here we describe the development of a prototype vaccine against capsular group B meningococcal infection based on a N. meningitidis isolate genetically engineered to have constitutive expression of the outer membrane protein FetA. Deoxycholate outer membrane vesicles (dOMVs) extracted from cells cultivated in modified Frantz medium contained 21.8% PorA protein, 7.7% FetA protein and 0.03 μg LPS per μg protein (3%). The antibody response to the vaccine was tested in three mouse strains and the toxicological profile of the vaccine was tested in New Zealand white rabbits. Administration of the vaccine, MenPF-1, when given by intramuscular injection on 4 occasions over a 9 week period, was well tolerated in rabbits up to 50 μg/dose, with no evidence of systemic toxicity. These data indicated that the MenPF-1 vaccine had a toxicological profile suitable for testing in a phase I clinical trial.